REPRODUCTIVE BIOLOGY OF THE GOLD SPOTTED GRENADIER ANCHOVY, COILIA DUSSUMIERI (CUVIER AND VALENCIENNES), ALONG THE NORTHWEST COAST OF INDIA - Fernandez, Irene; Devaraj, M (Indian Journal of Fisheries, 2011)
Four major gonad maturation stages and within them eight minor maturity stages could be identifiedin Coilia dussumieri. Maturing and mature fish (E to H stages) develop only one batch of ova which isspawned in the first spawning act, and the new batch of ova developing at stage H would spawn withinsix months of the previous spawning. Spawning in the population as a whole is throughout the year asis evident from continuous recruitment and occurrence of maturing and mature fish. However, as therecruitment pattern shows, the larval survival is high in the calmer premonsoon season (March to May)and low in the turbulent southwest monsoon (June to August). The spawning and nursery grounds arearound the 40 m depth zone. Fecundity ranges from about 1,000 to 5,000 eggs per female at sizes rangingfrom 15.7 to 19.0 cm in total length respectively. The ripe ova in stage H measure 0.82 to 0.90 mm indiameter. The minimum length at first maturity is 12.0 mm, when the fish is 6 to 7 months old. The correlationin the linear relation between fecundity and length (r = 0.7187) and between fecundity and weight(r = 0.7621) is high. The overall ratio of males to females in the population was 1:0.75. The fecundity pertonne of spawning females in a single spawning is 253 X 10’ and the population fecundity for a singlespawning for the annual biomass of 12,483 tonnes of adult females is 3,158 X 10Â·. Since the spawninginterval of individual fish is assumed to be less than or about six months, the fecundity per tonne ofspawning females and the annual population fecundity is atleast twice the above values